Signaling Pathways Involved in Renal Oxidative Injury: Role of the Vasoactive Peptides and the Renal Dopaminergic System - Rukavina Mikusic, N. L. (J Signal Transduct, 2014)
The physiological hydroelectrolytic balance and the redox steady state in the kidney are accomplished by an intricate interaction between signals from extrarenal and intrarenal sources and between antinatriuretic and natriuretic factors. Angiotensin II, atrial natriuretic peptide and intrarenal dopamine play a pivotal role in this interactive network. The balance between endogenous antioxidant agents like the renal dopaminergic system and atrial natriuretic peptide, by one side, and the prooxidant effect of the renin angiotensin system, by the other side, contributes to ensuring the normal function of the kidney. Different pathological scenarios, as nephrotic syndrome and hypertension, where renal sodium excretion is altered, are associated with an impaired interaction between two natriuretic systems as the renal dopaminergic system and atrial natriuretic peptide that may be involved in the pathogenesis of renal diseases. The aim of this review is to update and comment the most recent evidences about the intracellular pathways involved in the relationship between endogenous antioxidant agents like the renal dopaminergic system and atrial natriuretic peptide and the prooxidant effect of the renin angiotensin system in the pathogenesis of renal inflammation.